Differentiating disseminated intravascular coagulation (DIC) with the fibrinolytic phenotype from coagulopathy of trauma and acute coagulopathy of trauma‐shock (COT/ACOTS). Issue 5 (15th May 2013) - Gando, S.; Wada, H.; Thachil, J.; ,
Summary Two concepts have been proposed for the hemostatic changes occurring early after trauma. Disseminated intravascular coagulation (DIC) with the fibrinolytic phenotype is characterized by activation of the coagulation pathways, insufficient anticoagulant mechanisms and increased fibrinolysis. Coagulopathy of trauma and acute coagulopathy of trauma‐shock (COT/ACOTS) occurs as a result of increased activation of the thrombomodulin and protein C pathways, leading to the suppression of coagulation and activation of fibrinolysis. Despite the differences between these two conditions, independent consideration of COT/ACOTS from DIC with the fibrinolytic phenotype is probably incorrect. Robust diagnostic criteria based on its pathophysiology are required to establish COT/ACOTS as a new independent disease concept. In addition, the independency of its characteristics, laboratory data, time courses and prognosis from DIC should be confirmed. Confusion between two concepts may be based on studies of trauma lacking the following: (i) a clear distinction of the properties of blood between the inside and outside of vessels, (ii) a clear distinction between physiologic and pathologic hemostatic changes, (iii) attention to the time courses of the changes in hemostatic parameters, (iv) unification of the study population, and (v) recognition that massive bleeding is not synonymous with coagulation disorders. More information is needed to elucidate the pathogenesis of these two entities, DIC with the fibrinolytic phenotype and COT/ACOTS after trauma. However, available data suggest that COT/ACOTS is not a new concept but a disease entity similar to or the same as DIC with the fibrinolytic phenotype.